Development Strategy Agropolitan to Optimization Local Product Base Competitivenes Product - Nawangsih Nawangsih (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The research objectives are: to know the implementation of regional development strategies, to know the leading agricultural commodities that are marketed, to identify the forms of local economic potential that can be developed and to analyze the competitive advantages of the competitiveness of the products produced. This type of qualitative research uses a case study approach. Research informants are interested parties related to agropolitan areas. The research location is in the agropolitan area of ​​Senduro District, Lumajang Regency. The results of the implementation research are in the form of cooperating and synergizing with traders, the main commodity is banana mas Kirana, creating business opportunities around the location. Another local economic potential is the large number of labor-intensive workers who work as agricultural product transporters. The competitive advantage of product competitiveness in the agropolitan market is that the fruit is fresh, of good quality, until it reaches consumers in prime condition. Products in the agropolitan market have advantages in terms of taste, appearance, because the soil and harvest methods are considered, so the products sold are good.